Cognitive and neuroimaging outcome of very prodromal dementia with Lewy bodies - Frédéric Blanc; Vincent Bouteloup; Claire Paquet; Marie Chupin; Florence Pasquier; Audrey Gabelle; Mathieu Ceccaldi; Paulo Loureiro de Sousa; Pierre Krolak-Salmon; Renaud David; Clara Fischer; Jean-François Dartigues; et al. (GeroScience, 2025)

Effects of tire particles on earthworm (Eisenia andrei) fitness and bioaccumulation of tire-related chemicals - Thibault Masset; Florian Breider; Mathieu Renaud; Jonas Müller; Alan Bergmann; Etienne Vermeirssen; William Dudefoi; Kristin Schirmer; Benoit J.D. Ferrari (Environmental Pollution, 2025)

Construction of a large road infrastructure in a metropolitan area; what can the analysis of community complaints to noise tell us? - Alexis Pinsonnault-Skvarenina; Véronique Guay; Renaud Leblanc-Guindon; Mathieu Carrier; Annelies Bockstael; Jean-Pierre Gagné; Tony Leroux (Environmental Impact Assessment Review, 2024)

Plant-TFClass: a structural classification for plant transcription factors - Romain Blanc-Mathieu; Renaud Dumas; Laura Turchi; Jérémy Lucas; François Parcy (Trends in Plant Science, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Animal disease surveillance: How to represent textual data for classifying epidemiological information - Sarah Valentin; Rémy Decoupes; Renaud Lancelot; Mathieu Roche (Preventive Veterinary Medicine, 2023)

Consensus Recommendations for Clinical Outcome Assessments and Registry Development in Ataxias: Ataxia Global Initiative (AGI) Working Group Expert Guidance - Thomas Klockgether; Matthis Synofzik; Saud Alhusaini; Mathieu Anheim; Irina Antonijevic; Tee Ashizawa; Luis Bataller; Mélanie Berard; Enrico Bertini; Sylvia Boesch; Pedro Braga-Neto; Emanuel Cassou; et al. (The Cerebellum, 2023)
To accelerate and facilitate clinical trials, the Ataxia Global Initiative (AGI) was established as a worldwide research platform for trial readiness in ataxias. One of AGI’s major goals is the harmonization and standardization of outcome assessments. Clinical outcome assessments (COAs) that describe or reflect how a patient feels or functions are indispensable for clinical trials, but similarly important for observational studies and in routine patient care. The AGI working group on COAs has defined a set of data including a graded catalog of COAs that are recommended as a standard for future assessment and sharing of clinical data and joint clinical studies. Two datasets were defined: a mandatory dataset (minimal dataset) that can ideally be obtained during a routine clinical consultation and a more demanding extended dataset that is useful for research purposes. In the future, the currently most widely used clinician-reported outcome measure (ClinRO) in ataxia, the scale for the assessment and rating of ataxia (SARA), should be developed into a generally accepted instrument that can be used in upcoming clinical trials. Furthermore, there is an urgent need (i) to obtain more data on ataxia-specific, patient-reported outcome measures (PROs), (ii) to demonstrate and optimize sensitivity to change of many COAs, and (iii) to establish methods and evidence of anchoring change in COAs in patient meaningfulness, e.g., by determining patient-derived minimally meaningful thresholds of change.

First validation of GEDI canopy heights in African savannas - Xiaoxuan Li; Konrad Wessels; John Armston; Steven Hancock; Renaud Mathieu; Russell Main; Laven Naidoo; Barend Erasmus; Robert Scholes (Remote Sensing of Environment, 2023)

Quantifying the sensitivity of L-Band SAR to a decade of vegetation structure changes in savannas - Konrad Wessels; Xiaoxuan Li; Alexandre Bouvet; Renaud Mathieu; Russell Main; Laven Naidoo; Barend Erasmus; Gregory P. Asner (Remote Sensing of Environment, 2023)

Telemetry reveals the habitat selected by immature dragonflies: implications for conservation of the threatened dragonfly Leucorrhinia caudalis (Odonata: Anisoptera) - Aurélia LeNaour; Renaud Baeta; Eric Sansault; Mathieu Deville; Sylvain Pincebourde (Journal of Insect Conservation, 2019)

Identifying genomic hotspots of differentiation and candidate genes involved in the adaptive divergence of pea aphid host races - Pierre Nouhaud; Mathieu Gautier; Anaïs Gouin; Julie Jaquiéry; Jean Peccoud; Fabrice Legeai; Lucie Mieuzet; Carole M. Smadja; Claire Lemaitre; Renaud Vitalis; Jean‐Christophe Simon (Molecular Ecology, 2018)
Identifying the genomic bases of adaptation to novel environments is a long‐term objective in evolutionary biology. Because genetic differentiation is expected to increase between locally adapted populations at the genes targeted by selection, scanning the genome for elevated levels of differentiation is a first step towards deciphering the genomic architecture underlying adaptive divergence. The pea aphid Acyrthosiphon pisum is a model of choice to address this question, as it forms a large complex of plant‐specialized races and cryptic species, resulting from recent adaptive radiation. Here, we characterized genomewide polymorphisms in three pea aphid races specialized on alfalfa, clover and pea crops, respectively, which we sequenced in pools ( poolseq ). Using a model‐based approach that explicitly accounts for selection, we identified 392 genomic hotspots of differentiation spanning 47.3 Mb and 2,484 genes (respectively, 9.12% of the genome size and 8.10% of its genes). Most of these highly differentiated regions were located on the autosomes, and overall differentiation was weaker on the X chromosome. Within these hotspots, high levels of absolute divergence between races suggest that these regions experienced less gene flow than the rest of the genome, most likely by contributing to reproductive isolation. Moreover, population‐specific analyses showed evidence of selection in every host race, depending on the hotspot considered. These hotspots were significantly enriched for candidate gene categories that control host–plant selection and use. These genes encode 48 salivary proteins, 14 gustatory receptors, 10 odorant receptors, five P450 cytochromes and one chemosensory protein, which represent promising candidates for the genetic basis of host–plant specialization and ecological isolation in the pea aphid complex. Altogether, our findings open new research directions towards functional studies, for validating the role of these genes on adaptive phenotypes.

Estimating fractional cover of plant functional types in African savannah from harmonic analysis of MODIS time-series data - Sa’ad Ibrahim; Heiko Balzter; Kevin Tansey; Narumasa Tsutsumida; Renaud Mathieu (International Journal of Remote Sensing, 2018)

Optimizing control programmes by integrating data from fine-scale space use by introduced predators - Mariano R. Recio; Richard F. Maloney; Renaud Mathieu; Emilio Virgós; Antoni B. Moore; Philip J. Seddon (Biological Invasions, 2017)

Characterization of suspended particulate matter in the Moselle River (Lorraine, France): evolution along the course of the river and in different hydrologic regimes - Mathieu Le Meur; Emmanuelle Montargès-Pelletier; Allan Bauer; Renaud Gley; Sylvie Migot; Odile Barres; Claire Delus; Frédéric Villiéras (Journal of Soils and Sediments, 2016)

Quantifying fine-scale resource selection by introduced feral cats to complement management decision-making in ecologically sensitive areas - Mariano R. Recio; Renaud Mathieu; Emilio Virgós; Philip J. Seddon (Biological Invasions, 2014)

Quantifying fine-scale resource selection by introduced European hedgehogs (Erinaceus europaeus) in ecologically sensitive areas - Mariano Rodriguez Recio; Renaud Mathieu; M. Cecilia Latham; A. David M. Latham; Philip J. Seddon (Biological Invasions, 2013)

On‐land habitat preferences of female New Zealand sea lions at Sandy Bay, Auckland Islands - Amélie A. Augé; B. Louise Chilvers; Renaud Mathieu; Antoni B. Moore (Marine Mammal Science, 2012)
Terrestrial habitat is important for breeding in most pinnipeds. On land, most species remain near the shore, but New Zealand (NZ) sea lions, Phocarctos hookeri , often rest inland up to 1.5 km from the sea. Only three breeding areas of NZ sea lions exist today after the species was extirpated from its historical range (NZ mainland). The study was conducted at the Sandy Bay breeding colony, Auckland Islands, between December 2002 and March 2003. We used daily Global Positioning System locations of breeding females with pups and mapping in a Geographic Information System to determine terrestrial habitat use and preferences. Slopes less than 20° were preferred throughout the study. Females chose nursing sites with a seasonal change, preferentially based on the distance from the sea and habitat type. Comparisons with the other breeding colonies of NZ sea lions are presented and data are discussed in the context of the recolonization of the NZ mainland. Overall, the most suitable terrestrial habitat configuration for a breeding aggregation of NZ sea lions appears to be a sandy beach, with a wide area above high tide and moderate intertidal zone (for breeding), backed with vegetated sand dunes and forest on primarily flat terrain (for later dispersion).

Design of a GPS backpack to track European hedgehogs Erinaceus europaeus - Mariano R. Recio; Renaud Mathieu; Philip J. Seddon (European Journal of Wildlife Research, 2011)

Cost and Efficiency of Large Mammal Census Techniques: Comparison of Methods for a Participatory Approach in a Communal Area, Zimbabwe - Nicolas Gaidet-Drapier; Hervé Fritz; Mathieu Bourgarel; Pierre-Cyril Renaud; Pierre Poilecot; Philippe Chardonnet; Craig Coid; Denys Poulet; Sébastien Le Bel (Biodiversity and Conservation, 2006)